A boundary integral equation for the exterior neumann problem on multiply connected region - 493195 Chye, Mei Sian; Ali Hassan Mohamed Murid; Fakulti Sains (2011)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2010